Encouraging Walkability through a Collaborative Approach to Health Impact Assessments (symposia). (December 2017) - Tang, Joyce; Gondek, Jyoti; Charlton, Rick; Vandervelde, Amy; Tang, Joyce
Abstract : Background: Guided by the principles of the internationally recognized Urban Land Institute (ULI) Building Healthy Places toolkit, the City of Calgary developed a Health Impact Assessment (HIA) tool in 2016 that promotes walkable community design. Working with community partners and the landowner, City Administration was able to pilot the HIA in a greenfield development area to meet the walkability and wellness goals of the Municipal Development Plan. Since then, City Council has mandated that Administration continue to work with stakeholders to identify practices and/or policy that would encourage healthier, more walkable communities by leveraging the HIA tool. Aims: (1) Use the case of Nose Creek Area Structure Plan (ASP) in Calgary to illustrate the case for collaborative approaches to encourage walkability and healthy community design; (2) Explain the value that each stakeholder group brings to the process, as well as their ongoing roles in promoting walkability; (3) Frank discussion of obstacles and points of difference between stakeholders. Summary: This session will begin with an introduction from the City of Calgary project manager who spearheaded the effort for an HIA tool. Next, presenters will explain their reactions and experiences - positive and negative - to the use of the HIA as a tool to prioritize walkability in a greenfield setting. The discussant will then outline the ways in which the HIA tool actually brought stakeholder groups together, and how the Council directive for collaboration is presently unfolding. The panel discussion will focus on overcoming challenges and realizing the value of collectively creating better communities with a focus on walkability and wellness. The audience will hear firsthand accounts of the struggles and victories that presenters experienced.